The Welsh Institute of Performance Science: A Decade of Integrated Knowledge Translation in Elite Sport. - Knight, Camilla J.; Pankow, Kurtis; Shearer, David A.; Bringer, Joy D.; Davies, Brian R.; Lewis, Owen C.; Woodfine, Stephen R.; Kilduff, Liam P. (Sports Medicine, 2025)
Sport science researchers and practitioners have noted a gap between research and practice for some time. Although several solutions have been proposed, few recommendations have been made for researchers to follow that are based on successful, long-term sport science research programmes aimed at translating research into practice. Therefore, the purpose of this article is to outline a decade of work completed by the Welsh Institute of Performance Science as an institute for sport-based integrated knowledge translation. The aim is to provide a framework for other researchers and institutes to follow when engaging with organisations for long-term research-to-practice partnerships. In addition to outlining the development and functioning of the Welsh Institute of Performance Science to guide others, limitations of the approach used are also presented and considered to facilitate the future development of sport-specific models of knowledge translation, ensuring that the excellent research conducted across the disciplines of sport science effectively impacts the work of practitioners. Plain Language Summary: In recent years, there has been an increasing focus on addressing the gap between research and practice within sport science and sport medicine. To date, however, there are few published examples detailing exactly how academic research might be integrated within sports organisations. This article explains how the Welsh Institute of Performance Science has attempted to do this using an adapted knowledge translation approach. Specifically, based on a decade of work, it is apparent that Welsh Institute of Performance Science has helped athletes, coaches, sport organisations and researchers engage in a collaborative process that gets research into the hands of practitioners and makes a substantial contribution to practice while still benefiting researchers.